2019
DOI: 10.4103/psychiatry.indianjpsychiatry_531_18
|View full text |Cite
|
Sign up to set email alerts
|

New-wave behavioral therapies in obsessive-compulsive disorder: Moving toward integrated behavioral therapies

Abstract: New-wave behavioral therapies in obsessive-compulsive disorders (OCDs) comprise of third-wave therapies and newer cognitive therapies (CTs). This review covers outcome studies published in English until December 2017. A total of forty articles on mindfulness-based CT, metacognitive therapy, acceptance and commitment therapy, and danger ideation reduction therapy in the form of single-case studies, case series, open-label trials, two-group comparison studies, and randomized controlled studies were included. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 73 publications
0
2
0
1
Order By: Relevance
“…Searches in MEDLINE, PsycINFO, PSYINDEX, Web of Science, CINAHL and CENTRAL are specified in the online supplemental material. We will perform also backward and forward citation searches of all included studies and relevant reviews 16 47 48. To find studies in the grey literature, we will contact the authors of included studies or relevant conference abstracts of unpublished studies identified through the database, backward or forward searches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches in MEDLINE, PsycINFO, PSYINDEX, Web of Science, CINAHL and CENTRAL are specified in the online supplemental material. We will perform also backward and forward citation searches of all included studies and relevant reviews 16 47 48. To find studies in the grey literature, we will contact the authors of included studies or relevant conference abstracts of unpublished studies identified through the database, backward or forward searches.…”
Section: Methodsmentioning
confidence: 99%
“…Further RCTs are also expected to be available soon 46. Previous reviews hint at the usefulness of MABPs for people with OCD 15 16 47 48. However, a systematic review of all available evidence including a meta-analysis on the effectiveness of MABPs in the treatment of OCD is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Patří v celosvětovém měřítku mezi hlavní příčiny postižení (15), je významným osobním, sociálním a zdravotním problémem a je spojená s vysokou mírou psychiatrické komorbidity, zejména s depresivní poruchou a s úzkostnými poruchami (16)(17)(18)(19)(20). Dobře ověřenou metodou volby je spolu s medikací kognitivně behaviorální terapie s expozicemi a zábranou odpovědi (ERP; Exposure and Response Prevention) (11,(21)(22)(23)(24)(25)(26)(27). Odpověď pacientů na léčbu bývá různá a bohužel často přetrvávají reziduální příznaky (1,2).…”
Section: úVodunclassified